2014
DOI: 10.1186/1471-2474-15-342
|View full text |Cite
|
Sign up to set email alerts
|

Multiple plexiform schwannomas in the plantar aspect of the foot: case report and literature review

Abstract: BackgroundPlexiform schwannoma (PS) is a rare, peripheral nerve sheath tumor arranged in a plexiform pattern.Case presentationWe report an unusual case of a 19-year-old woman, who complained of pain in the plantar aspect of the left foot. Magnetic resonance image (MRI) demonstrates three solitary nodules of varying sizes in the deep soft tissue of the plantar aspect of the foot that are homogeneously isointense to skeletal muscle on T1-weighted images and hyperintense on T2-weighted fat-suppressed images, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…These tumors present as single, soft-to-rubbery, movable, non-tender and sometimes painful nodules [3]. Trauma may play an etiological role in the formation of these lesions [2]. Most PSs are small, with a maximum diameter of approximately 2 cm and originate from superficial nerves [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These tumors present as single, soft-to-rubbery, movable, non-tender and sometimes painful nodules [3]. Trauma may play an etiological role in the formation of these lesions [2]. Most PSs are small, with a maximum diameter of approximately 2 cm and originate from superficial nerves [4].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is a useful tool in the diagnosis of PS; the rims of PS nodules are smooth, and features of the lesions are similar to those of peripheral nerve sheath tumors, including heterogenous hyper- or iso-intensity to subcutaneous fat on T2-weighted MR images. It is reported that multinodular growth patterns in a single lesion and evident cystic degeneration on T2-weighted image are characteristics of PS, which are helpful in the differential diagnosis of these tumors [2]. PS consists of multiple intradermal or subcutaneous nodules composed primarily of cellular Antoni A regions with nuclear palisading and Verocay bodies [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 , 5 ]. Plexiform schwannoma usually presents as an isolated finding, and although it is unassociated with NF1, it may occur in the setting of NF2 and schwannomatosis [ 3 , 6 10 ]. Malignant transformation in plexiform schwannoma has not been described, whereas plexiform neurofibroma carries a significant risk of malignant transformation, especially in NF1 patients, making this distinction important [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%